DESCRIPTIVE MODELS OF THE PRESENTATION OF COGNITIVE SPACE “NATURE” IN BORIS GREBENSHCHIKOV’S IDIOSTYLE - Leszczak, Swietłana (Acta Neophilologica, 2017)
This paper discusses the distinction between the function of a descriptive artistic model and the explicative schemes of its realization. The descriptive model is considered as a structural-model function responsible for the cognitive representation of reality that is pictured in a text, a series of texts, creative output of an author, or a certain artistic trend. Semantics of a descriptive model is always connected to some cognitive space of the picture of the world. Based on the example of cognitive space “nature”, the author focuses on the descriptive model of the presentation of this cognitive space employed by Boris Grebenshchikov in his poetic texts. Moreover, the author determines the concepts of nature most relevant to the poet’s idiostyle.